2020
DOI: 10.1016/j.heliyon.2020.e04857
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of medium- and long-term mortality in elderly patients with acute pulmonary embolism

Abstract: Introduction Data on medium- and long-term prognostic factors for death in elderly patients with acute Pulmonary Embolism (APE) are lacking. The present study aimed to assess sPESI score and the Charlson Comorbidity Index (CCI) as medium- and long-term predictors of mortality in elderly patients with haemodinamically stable APE. Methods All consecutive patients aged≥65 years old, evaluated at the emergency department (ED) of our hospital from 2010 through 2014, with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
6
1
Order By: Relevance
“…They found that a CCI ≥ 1.00 was able to independently predict mortality at each of these endpoints and that sPESI failed to predict mortality at each of these endpoints. 25 We also did not find the sPESI score able to independently predict mortality at any endpoint in our multivariate analysis, however in our cohort the PESI score was independently associated with mortality at both short-, medium-, and long-term endpoints. The CCI was independently associated with overall mortality.…”
Section: Discussioncontrasting
confidence: 83%
“…They found that a CCI ≥ 1.00 was able to independently predict mortality at each of these endpoints and that sPESI failed to predict mortality at each of these endpoints. 25 We also did not find the sPESI score able to independently predict mortality at any endpoint in our multivariate analysis, however in our cohort the PESI score was independently associated with mortality at both short-, medium-, and long-term endpoints. The CCI was independently associated with overall mortality.…”
Section: Discussioncontrasting
confidence: 83%
“…There are multiple different criteria and scores for the risk stratification of pulmonary embolism, and the clinical indicators observed by the corresponding criteria and scores are not the same. A comprehensive assessment of risk stratification as recommended by the earliest guidelines for the diagnosis, treatment, and prevention of pulmonary thromboembolism was previously performed ( 8 ), with patients being classified into a high-risk group (with shock or hypotension), middle-high-risk group (stable hemodynamics but positive laboratory indicators and imaging), medium-low risk group (stable hemodynamics, with single positive laboratory indicators or imaging), and low-risk group (stable hemodynamics but no laboratory indicators or imaging abnormalities). There are also several other kinds of complicated scores for assessment of pulmonary embolism used at present ( 9 , 10 ).…”
Section: Formulation Of the Subsequent Treatment Plan After Definite ...mentioning
confidence: 99%
“…The researchers were interested in developing tools for estimating the risk of medium-and long-term mortality, which is of paramount importance for contribution to clinical decision-making regarding specific/tailored treatment regimes, and optimum follow-up. Despite the availability of data on short-term prognosis, only a few reports investigated the mortality predictors beyond the first 30 days after the insult of PE [6,7]. Characteristically, mortality rates >30% after five years of acute PE have been reported, which corresponds to a 2.5-fold increase in the risk of mortality in comparison to age-and gender-matched general population [8].…”
Section: Introductionmentioning
confidence: 99%